Physical principles of wireless communications - Granatstein, V. L. (Victor L.), 1935- (Boca Raton, FL : CRC Press, 2012)
'Preface to the second edition The technology of wireless communications is changing rapidly. In the less than 5 years that have elapsed since the writing of the first edition of this book'smart phones' with internet access have become ubiquitous making it appropriate to add material in the first chapter describing third generation (3G) and fourth generation (4G) cell phone systems. Beyond that natural update, I have received many suggestions for adding new material on topics that were treated lightly or omitted in the first edition. Primary among these were discussions of the relation between the basic laws of quantum and relativistic physics and the engineering of modern wireless communication systems. A section has been added describing Planck's Law of Blackbody Radiation. This has been followed by a detailed description of the assumptions made to derive from this law the engineering estimates of noise pickup by a communications receiver. Discussions of both General Relativity and Special Relativity have been expanded in the context of synchronizing clocks on the earth and in a satellite. A Global Positioning System (GPS) cannot be successfully designed without taking relativistic effects into account. The chapter on antennas has been made more complete by adding a section on wire loop antennas. In the chapter on statistical design, the discusson of shadowing correlations and their effect on cell phone system design has been expanded'--
Includes bibliographical references and index.
Keywords: Wireless communication systems